Effect of mangiferin, a naturally occurring glucoxylxanthone, on fear memory in rats - Pardo Andreu, Gilberto L; Maurmann, Natasha; Reolon, Gustavo Kellermann; de Farias, Caroline Brunetto; Delgado, René; Roesler, Rafael (Arzneimittelforschung, 2011)
Mangiferin (1,3,6,7-tetrahydroxy-2-[3,4,5-trihydroxy-6-(hydroxymethyl)oxan-2-yl]-xanthen-9-one, CAS 4773-96-0), a naturally occurring glucosylxanthone, is widely distributed in higher plants and a constituent of folk medicine. In the present study the effect of systemic administration of mangiferin on behavioural outcomes of neurological function in normal rats was investigated. A single intraperitoneal injection of mangiferin (10, 50 and 100 mg/kg body weight) immediately post-training produced an impairment of long-term memory for aversive training and a reduced freezing in a dose independent manner, when given immediately post-training. The administration of mangiferin 6 h post-training did not affect fear memory. The results indicate that mangiferin might induce deficits of emotionally motivated memory.
Keywords: C-glucosylxanthone; Inhibitory avoidance; Mangifera indica L.; Mangiferin; Memory